Challenges for Islamic Religious Education Lecturers in Using an Inquiry-Based Scientific Approach to Medical Faculty Students in the Digital Era - Sri Maryati; Abdullah Idi; Saipul Annur (Tarbawi : Jurnal Ilmu Pendidikan, 2026)
This study aims to describe the challenges of implementing an inquiry-based scientific approach in Islamic Religious Education (PAI) courses for medical students in the digital era, particularly when teaching abstract and normative Islamic aqeedah concepts. The research employed a qualitative, phenomenological approach. Data were collected through participant observation, structured interviews, and documentation. Interviews were conducted with eight lecturers from the Faculty of Islamic Religious Education at the University of Muhammadiyah Palembang's Faculty of Medicine. The data analysis used is thematic qualitative analysis, namely identifying, analyzing, and reporting data according to themes that appear from students' learning experiences. The analysis steps used were data collection, data presentation, data verification, and conclusion drawing. Initially, data were collected using structured interviews, followed by observations of the inquiry learning process using a scientific approach, and a review of student assignment/project documents. The data were then summarized into field notes, followed by source triangulation to verify their accuracy, and finally, conclusions were drawn. The results of the study show that Islamic Religious Education lecturers face the challenge of adapting to digital technology to develop superior Islamic Religious Education learning activities that are relevant to the knowledge and characteristics of medical students, amid limited and uneven learning resources. In addition to the ability to adapt to digital technology, Islamic Religious Education lecturers also face the challenge of being skilled in integrating scientific approaches and normative religious materials, empowering classroom facilitation skills, and fostering independent learning abilities in students. These findings recommend the need for a special forum for developing digital technology adaptation skills for Islamic Religious Education lecturers on a regular and continuous basis, especially for lecturers who teach students at the Faculty of Medicine.